2022
DOI: 10.1021/acsnano.2c04702
|View full text |Cite
|
Sign up to set email alerts
|

A High-Rate, Durable Cathode for Sodium-Ion Batteries: Sb-Doped O3-Type Ni/Mn-Based Layered Oxides

Abstract: O3-Type layered oxides are widely studied as cathodes for sodium-ion batteries (SIBs) due to their high theoretical capacities. However, their rate capability and durability are limited by tortuous Na+ diffusion channels and complicated phase evolution during Na+ extraction/insertion. Here we report our findings in unravelling the mechanism for dramatically enhancing the stability and rate capability of O3-NaNi0.5Mn0.5–x Sb x O2 (NaNMS) by substitutional Sb doping, which can alter the coordination environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 88 publications
2
67
0
1
Order By: Relevance
“…In situ charge and discharge XRD studies were conducted to further understand the crystal structure evolution of the NaNMS-0.05 electrode during cycling . The 3D counter graphs and related intensity contour maps (bird’s eye view) could show the phase change process (Figures a,b, Figures S16, S17).…”
Section: Resultsmentioning
confidence: 99%
“…In situ charge and discharge XRD studies were conducted to further understand the crystal structure evolution of the NaNMS-0.05 electrode during cycling . The 3D counter graphs and related intensity contour maps (bird’s eye view) could show the phase change process (Figures a,b, Figures S16, S17).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Nb and Sb ions have also been used as dopant to improve the electrochemical performance of layered oxide. [64,65] Shi et al [64] prepared Nb ion doped P2-type Na 0.78 Ni 0.31 Mn 0.67 Nb 0.02 O 2 . They found that Nb ion mostly doped at the particle surface, which could serve as a coating layer and protect the particle from electrolyte attack.…”
Section: Single Metal Ion Dopingmentioning
confidence: 99%
“…Recently, Nb and Sb ions have also been used as dopant to improve the electrochemical performance of layered oxide. [ 64,65 ] Shi et al. [ 64 ] prepared Nb ion doped P2‐type Na 0.78 Ni 0.31 Mn 0.67 Nb 0.02 O 2 .…”
Section: Ion Dopingmentioning
confidence: 99%
“…[20][21][22] The O-type Na x TMO 2 usually delivers a great capacity (≈160 to 220 mAh g −1 ) because of the high Na contents stacking sequence, however, it suffers from the sluggish Na + transport kinetics and fast capacity decay caused by unfavorable Na + diffusion pathway and complicated phase translation when going through the process of embedding and extracting Na + . [23][24][25][26] Compared with O-type, the P-type Na x TMO 2 is able to achieve a better rate and cycling performance because of the open prismatic structure which is a benefit to Na + mobility. [27][28][29] Whereas volume expansion occurring through irreversible P2-O2 phase translation at high voltage would result in the capacity decrease, which would hinder the achievement of high-energy density SIBs.…”
Section: Introductionmentioning
confidence: 99%